Field‐Aligned Currents in Auroral Vortices. Issue 2 (11th February 2021) - Johnson, Jay R.; Wing, Simon; Delamere, Peter; Petrinec, Steven; Kavosi, Shiva
Abstract: Auroral bright spots have been observed at Earth, Jupiter, and Saturn in regions that map to the magnetopause boundary layer. It has been suggested that the bright spots are associated with the Kelvin‐Helmholtz (KH) instability. We utilize a quasistatic magnetosphere‐ionosphere coupling model driven by a vortex in the boundary layer to determine how the field‐aligned current structure depends on ionospheric and boundary layer parameters. We compare vortex induced currents with shear‐flow induced currents. We find that the strength of the maximum currents are comparable, but the structure is significantly different. For a vortex, the current and electron precipitation maximize when the vortex size mapped to the ionosphere is approximately 1.5 L, where L ≡ Σ P / κ is the auroral scale length, Σ P is the Pedersen conductivity, and κ is the Knight parameter. For a vortex, the current width provides a direct measure of the size, Δ, of the boundary layer structure, while the current width of shear‐flow aurora is generally determined by the larger of Δ or L . For comparison with observations, an event is considered where auroral bright spots in the ionosphere are detected by DMSP SSUSI FUV when KH structures are observed on the dusk flank by THEMIS. Key Points: A model is developed that describes current systems associated with magnetospheric vortices and their dependence on ionospheric parameters There is a preferential vortex size that maximizes the current and electron flux Based on this model, auroral spot sizes are consistent with Kelvin‐Helmholtz structures detected in the boundary layers at Earth and Saturn